Визначення впливу гідрофобної компоненти на водоутримання в композитній системи, створеної на основі метилкремнезему та мікрокристалічної целюлози - Туров, В. В.; Зроль, Л. В.; Крупська, Т. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2022)
Heterogeneous composite systems created on the basis of nanosized methylsilica AM1-200 and microcrystalline cellulose were investigated using the method of low-temperature 1H NMR spectroscopy. Thermodynamic parameters of bound water in hydrated microcrystalline cellulose (MSC) powders and AM1/MSC composites at different ratios of hydrophobic and hydrophilic components were measured. It was established that the hydrophobic component is able to stabilize the aqueous system in the MSS/AM1 composite powders even when the amount of water is twice the amount of the solid phase. From the distributions of the radii of adsorbed water clusters, it follows that in highly hydrated composites, a significant part of the water is in the form of nanodroplets with a radius of several tens of nm